Mining expressed sequence tag (EST) microsatellite markers to assess the genetic differentiation of five Hynobius species endemic to Taiwan - Jou-An Chen; Pei-Ju Yu; Sheng-Wun Jheng; You-Zhu Lin; Pei-Wei Sun; Wen-Ya Ko; Chun-Fu Lin; Yu-Ten Ju (Scientific Reports, 2024)
Abstract Taiwan harbors five endemic species of salamanders (Hynobius spp.) that inhabit distinct alpine regions, contributing to population fragmentation across isolated “sky islands”. With an evolutionary history spanning multiple glacial-interglacial cycles, these species represent an exceptional paradigm for exploring biogeography and speciation. However, a lack of suitable genetic markers applicable across species has limited research efforts. Thus, developing cross-amplifying markers is imperative. Expressed sequence-tag simple-sequence repeats (EST-SSRs) that amplify across divergent lineages are ideal for species identification in instances where phenotypic differentiation is challenging. Here, we report a suite of cross-amplifying EST-SSRs from the transcriptomes of the five Hynobius species that exhibit an interspecies transferability rate of 67.67%. To identify individual markers exhibiting cross-species polymorphism and to assess interspecies genetic diversity, we assayed 140 individuals from the five species across 84 sampling sites. A set of EST-SSRs with a high interspecies polymorphic information content (PIC = 0.63) effectively classified these individuals into five distinct clusters, as supported by discriminant analysis of principal components (DAPC), STRUCTURE assignment tests, and Neighbor-joining trees. Moreover, pair-wise FST values > 0.15 indicate notable between-cluster genetic divergence. Our set of 20 polymorphic EST-SSRs is suitable for assessing population structure within and among Hynobius species, as well as for long-term monitoring of their genetic composition.